Exploring the landscape of diazabicyclooctane (DBO) inhibition: Avibactam inactivation of PER-2 β-Lactamase - Ruggiero, Melina (2017)
PER β -lactamases are an emerging family of extended-spectrum β -lactamases (ESBL) found in Gram-negative bacteria. PER β -lactamases are unique among class A enzymes as they possess an inverted omega (?) loop and extended B3 β -strand. These singular structural features are hypothesized to contribute to their hydrolytic profile against oxyimino-cephalosporins (e.g., cefotaxime and ceftazidime). Here, we tested the ability of avibactam (AVI), a novel non- β -lactam β -lactamase inhibitor to inactivate PER-2. Interestingly, the PER-2 inhibition constants (i.e., k2/K = 2 × 103 ±0.1 × 103 M-1 s-1, where k2 is the rate constant for acylation (carbamylation) and K is the equilibrium constant) that were obtained when AVI was tested were reminiscent of values observed testing the inhibition by AVI of class C and D β -lactamases (i.e., k2/K range of =103 M-1s-1) and not class A β -lactamases (i.e., k2/K range, 104 to 105 M-1s-1). Once AVI was bound, a stable complex with PER-2 was observed via mass spectrometry (e.g., 31,389 ± 3 atomic mass units [amu] ¡ 31,604 ± 3 amu for 24 h). Molecular modeling of PER-2 with AVI showed that the carbonyl of AVI was located in the oxyanion hole of the β -lactamase and that the sulfate of AVI formed interactions with the β-lactam carboxylate binding site of the PER-2 β -lactamase (R220 and T237). However, hydrophobic patches near the PER-2 active site (by Ser70 and B3-B4 β -strands) were observed and may affect the binding of necessary catalytic water molecules, thus slowing acylation (k2/K) of AVI onto PER-2. Similar electrostatics and hydrophobicity of the active site were also observed between OXA-48 and PER-2, while CTX-M-15 was more hydrophilic. To demonstrate the ability of AVI to overcome the enhanced cephalosporinase activity of PER-2 β-lactamase, we tested different β -lactam-AVI combinations. By lowering MICs to ≤2 mg/liter, the ceftaroline-AVI combination could represent a favorable therapeutic option against Enterobacteriaceae expressing blaPER-2. Our studies define the inactivation of the PER-2 ESBL by AVI and suggest that the biophysical properties of the active site contribute to determining the efficiency of inactivation.